2019
DOI: 10.1111/jcmm.14370
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of spliceosome U2AF1 significantly inhibits the development of human erythroid cells

Abstract: U2AF1 (U2AF35) is the small subunit of the U2 auxiliary factor (U2AF) that constitutes the U2 snRNP (small nuclear ribonucleoproteins) of the spliceosome. Here, we examined the function of U2AF1 in human erythropoiesis. First, we examined the expression of U2AF1 during in vitro human erythropoiesis and showed that U2AF1 was highly expressed in the erythroid progenitor burst‐forming‐unit erythroid (BFU‐E) cell stage. A colony assay revealed that U2AF1 knockdown cells failed to form BFU‐E and colony‐forming‐unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Genes involved in pre-mRNA splicing, response to unfolded protein, and intrinsic apoptotic signaling pathway in response to ER stress were significantly upregulated in homozygous U2af1 KO cells but not in heterozygous U2af1 KO cells compared to control cells (Supplemental Table 3). Upregulation of genes involved in apoptosis was consistent with the previous report of U2AF1 knockdown in human erythroblasts (35) and our observed increase in apoptotic (annexin V + , viability-marker -) KL cells in the Vav1-Cre/U2af1 flox/flox mouse fetal liver cells compared to Vav1-Cre/U2af1 wt/flox , U2af1 flox/flox and Vav1-Cre cells (Supplemental Figure 2D).…”
Section: U2af1 Deletion Dysregulates the Expression Of Genes Involved In Splicing Unfolded Protein Response And Apoptosissupporting
confidence: 92%
“…Genes involved in pre-mRNA splicing, response to unfolded protein, and intrinsic apoptotic signaling pathway in response to ER stress were significantly upregulated in homozygous U2af1 KO cells but not in heterozygous U2af1 KO cells compared to control cells (Supplemental Table 3). Upregulation of genes involved in apoptosis was consistent with the previous report of U2AF1 knockdown in human erythroblasts (35) and our observed increase in apoptotic (annexin V + , viability-marker -) KL cells in the Vav1-Cre/U2af1 flox/flox mouse fetal liver cells compared to Vav1-Cre/U2af1 wt/flox , U2af1 flox/flox and Vav1-Cre cells (Supplemental Figure 2D).…”
Section: U2af1 Deletion Dysregulates the Expression Of Genes Involved In Splicing Unfolded Protein Response And Apoptosissupporting
confidence: 92%
“…However, there was no significant difference between the two groups, which was probably related to the small sample size. Zhang et al 22 have shown that U2AF1 mutation can affect the expression of p53 signaling pathway and MAPK signaling pathway proteins by down-regulating the transcription of related genes. Therefore, we speculate that Q157P mutation of U2AF1 may lead to genetic instability and increase the incidence of some specific pathogenic genes by down-regulating the transcription of related genes, thus affecting the progress and prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“… 26 More importantly, the link with U2AF1 and erythropoiesis was further explored in a series of assays by Zhang et al, who demonstrated that U2AF1 plays a critical role in erythropoiesis through regulation of alternative splicing, which was further highlighted by the fact that it was significantly expressed in the progenitor burst-forming-unit and colony-forming-unit stages of erythroid maturation. 27 …”
Section: Discussionmentioning
confidence: 99%